2023
DOI: 10.3389/fped.2023.1122460
|View full text |Cite
|
Sign up to set email alerts
|

Detection of enterovirus in cerebrospinal fluids without pleocytosis in febrile infants under 3 months old reduces antibiotherapy duration

Abstract: BackgroundInfants under 3 months old with fever often receive empirical antibiotic treatment. Enterovirus is one of the leading causes of infection and aseptic meningitis but is not systematically screened. We aimed to evaluate enterovirus positive RT-PCR proportion in cerebrospinal fluid (CSF) with no pleocytosis and its impact on antibiotic treatment duration.MethodsDuring the enterovirus endemic season, from 2015 to 2018, we retrospectively studied infants under 3 months old, consulting for fever without ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A recent French study found that febrile infants without CSF pleocytosis who tested positive for EV received a shorter duration of antibiotics than those who were either not tested or tested negative. 7 Most EV cases are benign and can be easily treated at home with supportive measures and reassurance. Timely, ideally in-house availability of EV RT-PCR may facilitate early discharge home.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent French study found that febrile infants without CSF pleocytosis who tested positive for EV received a shorter duration of antibiotics than those who were either not tested or tested negative. 7 Most EV cases are benign and can be easily treated at home with supportive measures and reassurance. Timely, ideally in-house availability of EV RT-PCR may facilitate early discharge home.…”
Section: Discussionmentioning
confidence: 99%
“…6 This study highlights the importance of systematically testing for EV in febrile infants. A systematic review in 2017 7 found that routine EV testing was associated with decreased hospital stay and cost savings in febrile infants under 3 months. A recent French study found that febrile infants without CSF pleocytosis who tested positive for EV received a shorter duration of antibiotics than those who were either not tested or tested negative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation